Implementation of Shape – Based Matching Vision System in Flexible Manufacturing System - Lim Wee, Teck; Sulaiman , Marizan; Mohd Shah, Hairol Nizam; Omar , Rosli (www.jestr.org, 2010)
This research is regarding the application of a vision algorithm to monitor the operations of a system in order to control the decision making concerning jobs and work pieces recognition that are to be made during system operation in real time. This paper stress on the vision algorithm used which mainly focus on the shape matching properties of the product. The main focus of this paper is on the development of an adaptive training phase of the vision system, which is the creation of a flexible Region of Interest capability that is able to adapt to various type of applications and purposes depending on the users’ requirements. Additionally, an independent stand-alone control scheme was used to enable this system to be used in various types of manufacturing configurations. The system was tested on a number of different images with various characteristics and properties to determine the reliability and accuracy of the system in respect to different conditions and combination of different training traits.